Microplastic contamination in Auckland (New Zealand) beach sediments. (February 2020) - Bridson, James H.; Patel, Meeta; Lewis, Anita; Gaw, Sally; Parker, Kate
Abstract: We report the first large-scale investigation of microplastic contamination in beach sediments across Auckland, New Zealand's most populous region. Sediment samples were taken from the high tide and intertidal zones at 39 sites across estuary, harbour and ocean environments of the East and West Coasts. Microplastic contamination was present at the majority of beaches studied with a mean abundance of 459 particles.m − 2 ranging from 0 to 2615 particles.m − 2 . High variability was observed between the sites, indicating the importance of small-scale factors on microplastic contamination. Samples from high and intertidal zones showed no significant difference in microplastic contamination (p = 0.225). The West Coast beaches exhibited higher microplastic contamination compared with East Coast beaches (p = 0.004). Microplastics were predominately fibres (88%), with lower proportions of fragments (8%) and films (4%). The majority of the microplastics analysed were regenerated cellulose (34%), polyethylene terephthalate (22%) and polyethylene (15%). Graphical abstract: Unlabelled Image Highlights: We report on microplastic contamination of beach sediments in Auckland, New Zealand. Contamination was highly variable across sites ranging from 0 to 2615 particles.m − 2 . West Coast beaches exhibited higher contamination than East Coast beaches. Microplastic particles were predominately of fibre morphology.